Targeting of C‐type lectin‐like receptor 2 or P2Y12 for the prevention of platelet activation by immunotherapeutic CpG oligodeoxynucleotides. (13th April 2017) - Delierneux, C.; Donis, N.; Servais, L.; Wéra, O.; Lecut, C.; Vandereyken, M.; Musumeci, L.; Rahmouni, S.; Schneider, J.; Eble, J. A.; Lancellotti, P.; Oury, C.
Abstract : Essentials CpG oligodeoxynucleotide (ODN) immuotherapeutics cause undesired platelet activating effects. It is crucial to understand the mechanisms of these effects to identify protective strategies. CpG ODN‐induced platelet activation depends on C‐type lectin‐like receptor 2 (CLEC‐2) and P2Y12. Targeting CLEC‐2 or P2Y12 fully prevents CpG ODN‐induced platelet activation and thrombosis. Summary: Background: Synthetic phosphorothioate‐modified CpG oligodeoxynucleotides (ODNs) show potent immunostimulatory properties that are widely exploited in clinical trials of anticancer treatment. Unexpectedly, a recent study indicated that CpG ODNs activate human platelets via the immunoreceptor tyrosine‐based activation motif (ITAM)‐coupled receptor glycoprotein VI. Objective: To further analyze the mechanisms of CpG ODN‐induced platelet activation and identify potential inhibitory strategies. Methods: In vitro analyses were performed on human and mouse platelets, and on cell lines expressing platelet ITAM receptors. CpG ODN platelet‐activating effects were evaluated in a mouse model of thrombosis. Results: We demonstrated platelet uptake of CpG ODNs, resulting in platelet activation and aggregation. C‐type lectin‐like receptor 2 (CLEC‐2) expressed in DT40 cells bound CpG ODNs. CpG ODN uptake did not occur in CLEC‐2‐deficient mouse platelets. Inhibition of human CLEC‐2 with a blocking antibody inhibited CpG ODN‐induced platelet aggregation. CpG ODNs caused CLEC‐2 dimerization, and provoked its internalization. They induced dense granule release before the onset of aggregation. Accordingly, pretreating platelets with apyrase, or inhibiting P2Y12 with cangrelor or clopidogrel, prevented CpG ODN platelet‐activating effect. In vivo, intravenously injected CpG ODN interacted with platelets adhered to mouse injured endothelium, and promoted thrombus growth, which was inhibited by CLEC‐2 deficiency or by clopidogrel. Conclusions: CLEC‐2 and P2Y12 are required for CpG ODN‐induced platelet activation and thrombosis, and might be targeted to prevent adverse events in patients at risk.